The level of knowledge and application of tax planning by the accounting professionals of the city of Nova Serrana - MG (Research, Society and Development, 2020)
Given the current market scenario and increasingly fierce competitiveness, it is essential that companies know their economic and financial health. For such, their goals must be aligned with reducing waste, increasing productivity and profitability, and hence, improving the company conditions as a whole. Thus, with the high tax burden in Brazil, it is necessary the use of Tax Planning, which must be developed by a qualified professional. This study aims to analyze the level of knowledge and application of tax planning by accounting professionals. To test the hypotheses herein addressed, we applied a questionnaire to a sample of 25% of the population of accountants working in the footwear industry of Nova Serrana - MG, where the content addressed questions related to Tax Planning. We conclude that although accounting professionals know many of the tools needed to develop and apply efficient tax planning, such professionals choose to use only basic tools, not applying the more complex ones.